PEMBENTUKAN KARAKTER MUSLIM YANG EGALITER - Andi Herawati (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2021)
Prophet Muhammad Saw. who was sent by Allah Swt. bring Islam as a blessing for the universe. Rahmat which means goodness and enjoyment. This means when Allah swt. stated that Muhammad saw. as a grace means that Islam is a religion that brings goodness and enjoyment not only to humans but the entire universe. A person who embraces Islam is called a Muslim. A Muslim must understand and provide safety, welfare, goodness, enjoyment and peace to anyone and anything that is under the banner of Islam. Egalitarianism is the attitude of seeing someone as equal and equal, so that they do not underestimate, look down on and discriminate. This attitude of equality is a reflection or formed from faith in Allah Swt. which is manifested in the values ​​of love, empathy, brotherhood and unity in the frame of a sense of responsibility in living life and social life.